Efeito da fotobioestimulação sobre células musculares C2C12 submetidas à ação do veneno da serpente Bothrops jararacussu: mecanismos de reparo celular - Silva, Luciana Miato Gonçalves (2020)
Envenoming caused by Bothrops snakes is often associated with severe and complex local pathological manifestations, which include edema, blisters, dermonecrosis, hemorrhage and myonecrosis. The specific treatment for botropic accidents is the use of antivenom, but its action does not extend to local manifestations. Currently, data from the literature show that photobiomodulation (PBM), with low-level laser (LLL) has been shown to be an effective therapeutic tool against local effects caused by botropic venom. Thus, the present study investigated the effects of LLL on C2C12 myoblasts subjected to the action of B. jararacussu venom regarding its cell repair mechanism. To this end, the cells were incubated with the venom (12.5 μg/mL) and immediately irradiated once with the LLL at the wavelengths (λ) 660 nm and 780 nm, energy density 5 J/cm2, power of 20 mW, total energy 5.0 J, application time of 10 seconds per point and the cells were analyzed for 3, 6 and 24 h. The PBM promoted: (1) Increase in cell viability observed through cell count and cell migration observed by the scratch method in the cell layer; (2) favored muscle regeneration by increasing myogenic regeneration factors (Pax7, MyF5, MyoD and myogenin); (3) decreased levels of pro-inflammatory mediators IL-1, IL-6 and TNF-α and increased anti-inflammatory cytokine IL-10; (4) The expression of p38MAPK and caspase 3 was not altered by the treatment with PBM, however, this treatment caused a decrease in the expression of NF-κB; (5) reduction of oxidative stress, decreasing the production of H2O2 and nitric oxide and increasing the levels of Glutathione peroxidase (GPx), there was no difference between the expression of superoxide dismutase (SOD) and lipid peroxidation (TBars). Together, these results suggest that protection of the muscle cell by LBI seems to be related to the increase of myogenic factors as well as the modulation of inflammatory mediators and oxidative stress.